2007
DOI: 10.1073/pnas.0611419104
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic retention of gene expression patterns by the cell fate-determining transcription factor Runx2

Abstract: During cell division, cessation of transcription is coupled with mitotic chromosome condensation. A fundamental biological question is how gene expression patterns are retained during mitosis to ensure the phenotype of progeny cells. We suggest that cell fate-determining transcription factors provide an epigenetic mechanism for the retention of gene expression patterns during cell division. Runx proteins are lineage-specific transcription factors that are essential for hematopoietic, neuronal, gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
181
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(188 citation statements)
references
References 50 publications
7
181
0
Order By: Relevance
“…Furthermore, Runx2 up-regulation does not impede cell-cycle progression in cancer cells. In contrast, in normal osteoblasts, Runx2 ablation accelerates proliferation and increases ribosomal gene expression (18,19,29,30). Together these observations indicate that Runx2 may function as a tumor suppressor in some cell types and have oncogenic potential in others.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Furthermore, Runx2 up-regulation does not impede cell-cycle progression in cancer cells. In contrast, in normal osteoblasts, Runx2 ablation accelerates proliferation and increases ribosomal gene expression (18,19,29,30). Together these observations indicate that Runx2 may function as a tumor suppressor in some cell types and have oncogenic potential in others.…”
mentioning
confidence: 70%
“…Runx2, p53, and pRb all control cell proliferation by regulating cell-cycle progression and mediating cell growth through effects on ribosomal biogenesis (18,19,30,37,38). Abrogation of tumor suppressor pathways controlled by p53 and pRb, which are ubiquitously expressed, results in the development of diverse tumors that are confined to specific tissues (7,8), indicating that lineagespecific mechanisms are involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Runx2 controls the cell fate, proliferation, and growth through regulating ribosomal biogenesis (17,35). In Gli3…”
Section: Discussionmentioning
confidence: 99%
“…In Situ Hybridization-Preparation of 35 S-labeled uridine 5Ј-triphosphate and digoxigenin-UTP-labeled riboprobes, in situ hybridization, and image processing have been described previously (26). The Runx2-I probe used in in situ hybridization was prepared from a 639-bp fragment of murine Runx2 cDNA isolated from C3H10T1/2 cells by RT-PCR with the specific primers: 5Ј-CGGGATCCTCTCAGCTTTAGCGTCGTCA-3Ј for the forward primer and 5Ј-GCTCTAGACCGCAAGGG-ACTTGAAGTT-3Ј for the reverse primer.…”
Section: Methodsmentioning
confidence: 99%